The Sociology of Higher Education : Reproduction, Transformation and Change in a Global Era - David, Miriam; Naidoo, Rajani (Abingdon, Oxon : Routledge, 2013)
The Sociology of Higher Education: Reproduction, Transformation and Change in a Global Era provides an exciting and conceptually rich approach to the sociology of higher education. It offers innovative perspectives on the future of universities within the new and emerging research sub-field of the sociology of global higher education. The twenty-first century has witnessed wide-ranging structural and ideological transformations in higher education which have created both a sense of opportunity, as well as crisis and loss in the...
Includes index.
Keywords: Educational sociology; Education, Higher